The Influence of Servant Leadership and Organizational Justice on Teacher Performance Mediated by Teacher Job Loyalty - Meilando, Reksy; Nurhayati, Mafizatun; Listyarini, Sri (International Journal of Management and Digital Business, 2023)
Objectives: The purpose of this research is to analyze the effect of servant leadership, organizational justice, and loyalty on teacher effectiveness, as well as its role as a mediator in the relationship between servant leadership and organizational justice and teacher effectiveness. Methodology: The primary objective of this research is to scrutinize the influence of servant leadership, organizational justice, and loyalty on teacher effectiveness while also examining its function as a mediator in the impact of servant leadership and organizational justice on teacher effectiveness. The data analysis method employed in this research is Partial Least Squares (PLS).. Conclusion: The outcomes of this research can be summarized as follows: 1. Servant leadership exhibits a negative and statistically insignificant impact on teacher effectiveness, while organizational justice and workplace loyalty have a positive and statistically significant effect. 2. Both servant leadership and organizational justice demonstrate a positive and significant impact. 3. Job loyalty serves as a mediating variable between employee and organizational justice, affecting teacher performance. Conclusion: Job loyalty can serve as a mediator influencing the performance of teachers in the context of both servant leadership and organizational justice. Servant leadership and organizational justice promote job loyalty, thereby influencing teacher effectiveness. It is hoped that this research will be valuable as a contribution to the science of educational leadership, learning experiences, and information sharing for schools, relevant institutions, and readers in general